2020
DOI: 10.1007/s10591-019-09531-8
|View full text |Cite
|
Sign up to set email alerts
|

Financial Stress and the Relative Income Hypothesis Among Black College Students

Abstract: The majority of college students experience financial stress, but not all experience it with the same frequency or intensity. Research suggests Black students experience a greater intensity of financial stress than their White peers do. This study revealed a link between perception of relative consumption and financial stress among 965 Black students at 52 predominantly White colleges and universities in the United States. The relative income hypothesis (RIH) literature offers potential mediators of financial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…Thus, early intervention which is delivered “just‐in‐time” (Kalwij et al ., 2019) is necessary and universities have opportunity to better support students to build financial skills. This might be through offering targeted financial literacy programmes for university students, peer‐to‐peer financial coaching to improve financial behaviour (Britt et al ., 2011) or by establishing student financial wellness centres such as those at University of Missouri and Utah Valley University in the United States (White, 2020) to encourage budgeting and saving. Universities and policy‐makers could also work together to reduce financial stress on university students through promoting programmes and policies that minimise costs to students such as ancillary course fees, student accommodation, textbooks and travel (White, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, early intervention which is delivered “just‐in‐time” (Kalwij et al ., 2019) is necessary and universities have opportunity to better support students to build financial skills. This might be through offering targeted financial literacy programmes for university students, peer‐to‐peer financial coaching to improve financial behaviour (Britt et al ., 2011) or by establishing student financial wellness centres such as those at University of Missouri and Utah Valley University in the United States (White, 2020) to encourage budgeting and saving. Universities and policy‐makers could also work together to reduce financial stress on university students through promoting programmes and policies that minimise costs to students such as ancillary course fees, student accommodation, textbooks and travel (White, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Consumption is not only determined by the consumer's current income, but it is also influenced by the level of income compared to that of the past and those around them. According to the relative income hypothesis, the theory actually divides the income structure into current income and past income to examine the relationship between these two types of income on consumption [11,12]. So, when people determine the type of consumption, they are influenced by a combination of current and past income and the income of those around them.…”
Section: Relative Income Hypothesismentioning
confidence: 99%
“…Discontinuous enrollment refers to when students take gaps between their education to save up money. In fact, 40% of Black students reported that they needed extra time to finish their degree (White, 2020). According to White (2020), 70% of Black students are under financial stress.…”
Section: Lack Of Financial Resources (Poverty)mentioning
confidence: 99%